Retrospective cohort study of the efficacy and safety of dabigatran: real-life dabigatran use including very low-dose 75 mg twice daily administration - Yuuki Akagi; Tatsuo Chiba; Shusuke Uekusa; Hiroyoshi Kato; Shigeo Yamamura; Yukiko Aoki; Mizuho Enoki; Yuka Ogawara; Takanori Kasahara; Yuki Kimura; Tadahiro Shimizu; Aiko Takeishi; et al. (BMC, 2019)
Abstract Background Dabigatran is a direct thrombin inhibitor and an anticoagulant that is prescribed to prevent ischemic stroke and systemic embolism in non-valvular atrial fibrillation. Dabigatran (150 mg twice daily) is non-inferior to warfarin for the prevention of stroke and systemic embolism. A dose reduction to 110 mg twice daily should be considered for patients with decreased renal function, elderly patients, and those with a history of gastrointestinal bleeding. A small number of patients are prescribed 75 mg twice daily; however, excessive dose reduction below that indicated on the package insert may decrease the effectiveness of dabigatran. In this study, we investigated the incidence of thromboembolic events and hemorrhagic complications in patients receiving different doses of dabigatran, including patients receiving the very low-dose of 75 mg twice daily. Methods Five hospitals in Meguro and Setagaya areas of Tokyo were included in this study. The subjects were patients receiving dabigatran in the hospitals from March 2011 to February 2014. Thromboembolic events (stroke, systemic embolism, and transient cerebral ischemic attack) and hemorrhagic complications occurring before December 2014 were retrospectively evaluated. Results A total of 701 subjects received dabigatran during the study period: 187 patients (26.7%) received 150 mg twice daily (normal dose), 488 patients (69.6%) received 110 mg twice daily (low-dose), and 26 patients (3.7%) received 75 mg twice daily (very low-dose). Thromboembolism occurred in 4 (2.1%), 11 (2.3%), and 3 patients (11.5%), in the normal dose, low-dose, and very low-dose groups, respectively. The odds ratio of the 75 mg dose to the 150 and 110 mg doses was 5.73 (95% CI, 1.55-21.2; p = 0.009), and the incidence with the 75 mg dose was higher than that with the other doses. Although the number of events was limited, it should be noted that 3 patients in the very low-dose group had thromboembolic events. Conclusions The results suggest that sufficient anticoagulation efficacy may not be maintained when the dabigatran dose is excessively reduced to 75 mg twice daily.